Application of Improved Graph Theory in Planning of River and Lake System Connection - JIANG Yu; ZHANG Qionghai; YAN Meng (Renmin Zhujiang)
This paper first analyzes the river system characteristics,hydrodynamic conditions,and status quo of water environment in the tidal river network area.On this basis,a preliminary connection scheme is then drawn up by the concept of connectivity in the graph theory based on “flow resistance” and the connectivity diagnosis and optimization method of river systems based on the “shortest path” idea.The scheme is further refined by a one-dimensional hydrodynamic mathematical water quality model.The results reveal that the scheme of minimum resistance connection by the graph theory is the optimal scheme of structural connectivity,and the problem of connection failure caused by the sluice control mode is solved after the scheme is refined by the mathematical model.This method can quickly diagnose the structural connectivity of river and lake systems,enrich the diagnostic means of river and lake connectivity,and provide a reference for the planning of river system connectivity in the tidal river network area of the Pearl River Delta.